Determination of the optimum viewing distance for a multi-view auto-stereoscopic 3D display - Yoon, Ki-Hyuk; Ju, Heongkyu; Park, Inkyu; Kim, Sung-Kyu (OPTICAL SOC AMER, 2014)
We present methodologies for determining the optimum viewing distance (OVD) for a multi-view auto-stereoscopic 3D display system with a parallax barrier. The OVD can be efficiently determined as the viewing distance where statistical deviation of centers of quasi-linear distributions of illuminance at central viewing zones is minimized using local areas of a display panel. This method can offer reduced computation time because it does not use the entire area of the display panel during a simulation, but still secures considerable accuracy. The method is verified in experiments, showing its applicability for efficient optical characterization. (C) 2014 Optical Society of America